Studying Shape and Size The Udder VS Milk Production of (Alawassi race) in The Syrian Coast - Alkhayer, Khaled Mortada (Latakia University Journal -Biological Sciences Series, 2013)
A research had been made in three areas at the Syrian Cost where Al Awassi race is grown; these areas are (Arab Al Mulk, Dwer Al Khateeb, Bekhdarmow). The number of Al Awassi there reaches to (439) heads. The research was started at 2/11/2009, and a random sample of (82)was selected from each area (33-27-22) in a row, and measured were at the day number (30-90-150) during the season milking, and completed at 4/3/2010. Results showed at the second phase of day (90) a high measurements of udder which meets the maximum standards of milk production, and the udder specification had a significant impact on all forms of the mammary gland (20,01), as well as the nipple specification, order of milking season, and age had impact on the nipple’s size (20,01), but not on the length of it, but the season milking and age had effect on udder height above the ground (20,001). Results showed a correlation which is not fixed between the udder specifications and quantity of milk as well as a weak and positive relationship between the amount of milk and nipple measurements in the order of (r=0.33, r=0.49, r=0.19, r=0.27).